Thermal performance of the building envelope integrated with phase change material for thermal energy storage: an updated review. - Rathore P.K.S.; Gupta N.K.; Yadav D.; Shukla S.K.; Kaul S. (My University, 2025)
One of the major sources of end-use of energy in buildings is consumed in space cooling for improving indoor thermal comfort. Climate extremities like heat waves and extreme temperature events have further pushed the demand for energy in buildings. Therefore, the need of the hour is to develop energy-efficient building envelope for optimizing the end-use of energy in buildings.Enhancing the thermal energy storage capacity of the building envelope by incorporating PCM is one of the sustainable methodsof regulating indoor temperature. This work focuses on the applicability of PCM as a thermal energy storage building material. A detailed discussion on the importance of building envelope and thermophysical properties of the building material is presented in this study. This study highlights the fundamental concept of Phase Change Material, types, and thermophysical properties of Phase Change materials commonly used in building envelopes. Techniques used for the incorporation of the PCM and the principle of working of the PCM in the building envelope were also presented in this study. A comprehensive summary of up-to-date published literature in which PCM is directly incorporated in the building material is also conducted. Lastly, future recommendations based on identified research gaps were suggested. © 2022